Insights into coaching effectiveness: Perspectives from coaches and players in South African Women's Rugby - Solomons, J.; Bekker, S.; Groom, R.; Kraak, W. (International Journal of Sports Science & Coaching, 2025)
Sports coaching involves navigating ambiguity and uncertainty in stakeholders` perspectives and managing a dynamic micro-political environment. This study explores the relationship between coaching efficacy and effectiveness in South African Women's Rugby. It examines how a coach's belief in their ability to influence athlete learning and performance (coaching efficacy) correlates with the actual impact on athletes (coaching effectiveness). By aligning coaches` perceived competence with tangible athlete outcomes, the study provides insights into factors influencing coaching practices and athlete development. The study involved 28 women players (mean age: 24.8 ± 4.0 years) and 8 coaches (mean age: 41 ± 3.8 years) who participated in semi-structured online interviews. The interview script, derived from the Coaching Effectiveness Survey (CES) tool, was analysed using Braun and Clarke's 6-step process of thematic content analysis. Under the four efficacy dimensions, sub-themes emerged as follow: 1) motivation (climate created by the coach and a motivational climate experienced by the players), 2) technique (coaching physical, technical, and tactical aspects of rugby), 3) game strategy (guiding players to successful outcomes), and 4) character-building efficacy (cultivating a positive environment for sportswomanship and holistic development). The findings incorporate feedback from players and coaches, highlighting firsthand experiences of coaching effectiveness. This approach enables experts to identify effective coaching strategies and those needing refinement within Women's Rugby. The study's findings promise to inform future coach development frameworks and foster a comprehensive understanding of coaching effectiveness in the dynamic landscape of Women's Rugby worldwide.